Synchronised Cardioversion for Chronic Atrail Fibrillation - Aniteye, E.; Kotei, D.; Tettey, M.; Sereboe, L.; Edwin, F.; Doku, A.; Tamatey, M.; Entsuah- Mensah, K.; Batista, S.; Frimpong-Boateng, K. (Ghana Medical Journal, 2008)
Objective: To determine whether elective cardioversion was successful in establishing sinus rhythm in patients with chronic atrial fibrillation and the energy used for the cardioversion using a monophasic defibrillator. Design: This is a retrospective descriptive study. Setting: Intensive care unit of the National Cardiothoracic Centre, Korle-bu Teaching Hospital. Subjects: Twelve consecutive patients referred by physicians with chronic atrial fibrillation which had not responded appropriately to pharmacological agents. Method: Using the intensive care admissions and discharge register and report book, the patients case notes were retrieved. The pre-cardioversion echocardiography diagnosis and drugs were noted. The results of cardioversion, and the current rhythm status were also reviewed. Results: There were twelve elective cardioversions for chronic atrial fibrillation during the period under investigation. All the patients were on warfarin with INR- 2.2-2.8. Eight of the patients had initial echocardiographic evidence of thrombi in the left atrium. Sinus rhythm was established in 9(75%) of the patients. The mean energy used for the cardioversion was 384.4+167.7J. Of the 3 with failed cardioversion, one was later successfully cardioverted to sinus rhythm. On review, 9(75%) of the patients are still in sinus rhythm 6 months to 15 months after cardioversion. Six of these patients continue with oral amiodarone however. Conclusion: Synchronized cardioversion for chronic atrial fibrillation is safe and may be successful after failure of pharmacologic cardioversion in patients where sinus rhythm is desirable.
Journal Article
Keywords: Atrial fibrillation; synchronized cardioversion; monophasic defibrillator